Referenciais do querigma lucano no documento de Puebla: compreensão de evangelização - Lima, José Bartolomeu Felix de (2017)
The following search has as object of analysis the theme: “References of the kerygma lucano at the Puebla’s document: Understanding of evangelization”. The object of this research is relevant because it is a part of the Christianity’s central nucleus. And also because it appears in the New Testament’s Theology. Mainly at the gospels and at the Apostles’ Acts that are texts of the gender historical-kerygmatic.In the first chapter I am going to reflect about the term kerygma using the evangelist Lucas’ Theology. The texts that reference the kerygmatic statement of the lucana narrative are going to be studied using the historical critic methodology. It helps to understand the meaning of the message contributing for an authentic understanding and interpretation of the theme. In the second chapter I am going to reflect about the understanding of evangelization by the perspective of Puebla’s III Latin-American Conference. In the third chapter I am going to identify and correlate the understanding of evangelization of the Puebla’s III Latin-American Conference and the characteristics of the lucana theology.